System, Structure, and Contradiction: The Evolution of 'Asiatic' Social Formations - Friedman, Jonathan (Rowman & Littlefield Publishers, 2000)
The first edition of System, Structure, and Contradiction was an important step in merging the materialist determinism of the structuralist Marxists with the cultural, ideological approach favored by anthropologists. By reconciling these two traditionally warring schools of thought, the author provided a more nuanced understanding of the various factors that drive social change and social complexity. Though viewed through the lens of an ethnographic and historical case study of the Kachin of Burman, Friedman's theory has had a major impact on the work of archaeologists, anthropologists, world-systems scholars, and Marxist theorists alike. This new edition of Friedman's much-cited work contains the full text of the original volume (never published in North America) along with two related articles by the author, and a comprehensive new introduction that brings his theoretical notions, and the debate over this book, to the present. A classic work of anthropological and social theory, it will be of interest to scholars and their advanced students in anthropology and related disciplines.